A completely leucistic Rufous-bellied Thrush (Turdus rufiventris) breeding successfully in central-east Argentina - Colombo, Martín (2018)
Leucism is a color aberration characterized by the absence of pigmentation which can either be partial or complete. Abnormally colored birds have reduced chances of survival and mating success compared to normally colored individuals. We present a documented record of a complete leucistic adult Rufous-bellied Thrush (Turdus rufiventris) breeding successfully in Cariló, centraleast Argentina. In the winter of 2016 we observed a completely white thrush. In the subsequent spring we observed it collecting food and delivering it to two fledglings, which were normally colored. The adult thrush survived its own post-fledging period despite its increased predation risk due to conspicuousness, managed to get a breeding pair and breed successfully. Since reports of abnormally colored birds breeding in wild populations are rare, we emphasize the importance of making this information available.